Islanding detection method for multi‐terminal renewable power DC distribution system. Issue 10 (25th May 2021) - Ke, Jia; Jin, Sun; Zhiming, Shi; Zhengxuan, Zhu; Qijuan, Zhao; Tianshu, Bi
Abstract: Most of the traditional islanding detection methods are designed for renewable sources in AC systems and cannot be directly applied in multi‐terminal DC renewable power distribution systems. Moreover, the attenuation effect of multi‐branches makes it difficult for active methods to effectively detect complex islanding operations with multiple renewable power sources. To address the above problems, this paper proposes an active high‐frequency impedance estimation based DC islanding detection method. The impedance of converters is proved to be a constant value at high‐frequencies, and the high‐frequency impedance of the system changes significantly after islanding. Therefore, islanding operations can be accurately detected through impedance characteristics with a negligible none detection zone. The proposed islanding detection method uses DC/DC converters to inject non‐characteristic harmonics to perform high‐frequency impedance calculations without additional injection equipment. The high‐frequency impedance directly reflects structural changes of the DC system. In this case, this method has lower requirements on the disturbance intensity and will not be influenced by the attenuation effect. The injected harmonic voltage is used as an auxiliary criterion to detect complex DC islanding operations with multiple renewable sources. Simulation results prove that the proposed method has high detection accuracy and is not affected by transient conditions.